2014
DOI: 10.1186/1471-2431-14-135
|View full text |Cite
|
Sign up to set email alerts
|

Providing newborn resuscitation at the mother’s bedside: assessing the safety, usability and acceptability of a mobile trolley

Abstract: BackgroundDeferring cord clamping at very preterm births may be beneficial for babies. However, deferring cord clamping should not mean that newborn resuscitation is deferred. Providing initial care at birth at the mother’s bedside would allow parents to be present during resuscitation, and would potentially allow initial care to be given with the cord intact. The aim of this study was to evaluate the usability of a new mobile trolley for providing newborn resuscitation by describing the range of resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 11 publications
1
87
1
2
Order By: Relevance
“…The Bedside Assessment, Stabilisation and Initial Cardiorespiratory Support (BASICS) trolley can be lowered between the woman's legs or over an operating table and provides heat, suction and ventilation . When trialled, the trolley was able to be successfully used for resuscitation and cord integrity was maintained in most cases (Thomas et al, 2014). Neonatal temperature was maintained and practitioners reported better communication with parents, while parents gave positive feedback.…”
Section: Facilitationmentioning
confidence: 84%
“…The Bedside Assessment, Stabilisation and Initial Cardiorespiratory Support (BASICS) trolley can be lowered between the woman's legs or over an operating table and provides heat, suction and ventilation . When trialled, the trolley was able to be successfully used for resuscitation and cord integrity was maintained in most cases (Thomas et al, 2014). Neonatal temperature was maintained and practitioners reported better communication with parents, while parents gave positive feedback.…”
Section: Facilitationmentioning
confidence: 84%
“…Concerns about delayed resuscitation, thermal care and technical difficulties are being addressed through the development and trialling of new equipment to allow transition to be assisted closer to the mother with the cord intact 75 76. Studies have shown DCC to be feasible, safe and to have significant benefit to preterm infants, with no detriment from the risks above 20 77…”
Section: Postnatal Interventionsmentioning
confidence: 99%
“…In many instances, existing equipment is not designed for this and in some cases placental abruption or maternal conditions will prevent it. While the potential clearly exists, many questions remain about the impact especially on mothers and babies and equipment and staff requirements 31. These need to be answered before this approach can be accepted or implemented routinely.…”
Section: Ongoing Areas Of Uncertaintymentioning
confidence: 99%